Biogenic and Non-Biogenic Waste Utilization in the Synthesis of 2D Materials (Graphene, h-BN, g-C2N) and Their Applications - Singh, Manish Pratap; Bhardwaj, Abhishek Kumar; Bharati, Keval; Singh, Rahul Pratap; Chaurasia, Sujeet Kumar; Kumar, Santosh; Singh, Rishi Pal; Shukla, Abhishek; Naraian, Ram; Vikram, Kunwar (Frontiers in Nanotechnology, 2021)
There is a significant amount of waste generated which creates a huge environmental issue for humanity/earth and a tremendous number of varieties of resources of a different kind are needed globally. In this context, Nanoscience and Technology has shown its potential ability to solve the above issues and provides realistic applications and devices. The beauty of nanotechnology is its multidisciplinary approach, in which the green nanotechnology has been translated to focus on waste materials. The waste materials are generally generated from biogenic (rice husk, dead leaves, waste food, etc.) and non-biogenic (several types of plastics waste, lard oil, etc.) materials produced from municipal or industrial waste. Currently, a large number of efforts have been made to utilize the waste materials for the synthesis of 2D materials in a greener way. This green synthetic approach has two advantages (a) it reduces the cost of synthesis and (b) minimal use of hazardous chemicals. The biogenic wastes (contains biomolecules) are containing several significant constituents such as co-enzyme, enzyme, proteins, terpenoid etc. These constituents or bimolecular are known to play an energetic role in the formation of different variety of 2D materials and hence controlling the protocols of green synthesis of 2D materials. This review focuses on the exploration of the current understanding of 2D layered material synthesis methods using waste material produce from biogenic and non-biogenic waste. It also investigates the applications of various 2D layered materials in perspective with synthesis from waste and future challenges along with their limitations to the industrial-scale synthesis.